2016
DOI: 10.1002/anie.201605132
|View full text |Cite
|
Sign up to set email alerts
|

C−N Bond Formation from a Masked High‐Valent Copper Complex Stabilized by Redox Non‐Innocent Ligands

Abstract: The reactivity of a stable copper(II) complex bearing fully oxidized iminobenzoquinone redox ligands towards nucleophiles is described. In sharp contrast with its genuine low-valent counterpart bearing reduced ligands, this complex performs high-yielding C-N bond formations. Mechanistic studies suggest that this behavior could stem from a mechanism akin to reductive elimination occurring at the metal center but facilitated by the ligand: it is proposed that a masked high oxidation state of the metal can be sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 69 publications
1
15
0
1
Order By: Relevance
“…[42] It is postulated that no direct metal-CF 3 bond occurs because the reactivity differs from that of isolated species with this bond present. [43] Besides radical-radical coupling with TEMPO · ,c atalytic trifluoromethylation of alkynes, heteroaromatics andv inyl silyl ethers was reported as well. The complexes formed after electron transfer were spectroscopically investigated but not isolated.…”
Section: Catalytic Ligand-to-substrates Ingle-electron Transfermentioning
confidence: 99%
“…[42] It is postulated that no direct metal-CF 3 bond occurs because the reactivity differs from that of isolated species with this bond present. [43] Besides radical-radical coupling with TEMPO · ,c atalytic trifluoromethylation of alkynes, heteroaromatics andv inyl silyl ethers was reported as well. The complexes formed after electron transfer were spectroscopically investigated but not isolated.…”
Section: Catalytic Ligand-to-substrates Ingle-electron Transfermentioning
confidence: 99%
“…reported trifluoromethylation of Cu II (SQ) 2 [28] and application of the resulting unstable complex as a source of CF 3 radicals [29] . Stoichiometric reactions with aryl boronic acids gave N‐arylation products [30] …”
Section: Introductionmentioning
confidence: 99%
“…In a second contribution, the authors reported that the bis-iminobenzoquinone Cu II –CF 3 complex reacted with arylboronic acids to generate the C–N coupling product derived from the oxidation of the ligand scaffold (Figure 80, ii). 306 It was proposed that intramolecular CF 3 − transfer produced a copper(III) complex bearing the oxidized ligand scaffold and an iminosemiquinone radical species (species C in Figure 80). It was also implied that addition of PhB(OH) 2 could generate a copper(II) species with the phenyl bound to the copper in a trans position relative to the CF 3 group (species D in Figure 80).…”
Section: Cu-promoted Functionalization Of Organic Molecules Beyond Enmentioning
confidence: 99%